Pengaruh High Intensity Interval Training (HIIT) dan Continues Training Terhadap VO₂ Max Pada Pemain Basket Unit Bola Basket Universitas Muhammadiyah Surakarta - Kurniandani, Riki; , Dwi Rosella K.S., S.FT., M.Fis (2017)
Background: The game of basketball is played for 40 minutes which is divided into four quarters, with each quarter consisting of 10 minutes. To play the game of basketball, it is necessary to have a lot of stamina which can be seen from the value VO₂ Max. There are different types of exercises to improve VO₂ Max, such as high intensity interval training (HIIT) and Continues training. Objective: The objective is to know the difference between the effect of high intensity interval training (HIIT) and continues traning against VO₂ Max Of Basketball Players of Muhammadiyah University of Surakarta. Method: The method of this study uses pre and post tests of two groups designed, with a total sample of 9 basketball players as high intensity interval training (HIIT) group , and 10 players as continues training group taken using purposive sample.The high intensity interval training (HIIT) method is to run 30 seconds for the sprint interspersed with 30 seconds of jogging and is done alternately for 20 minutes. The continues training method is running at moderate intensity for 30 minutes. The duration of the exercise is as many as 3 times a week for 4 sundays. The measurement of the VO₂ Max is by using multistage fitness test, the comparative test data analysis using the wilcoxon signed ranks test and mann whitney test. Result: The results are the difference between pre-test and post-test in the group of high intensity interval training (HIIT) is 9.94, while the group continues training is 6.02. The result of statistic test, influences of high intensity interval training (HIIT) againts VO₂ with p = 0,008 and continues traning against VO₂ Max with p = 0,005. The difference from average VO₂ Max value from two groups with p = 0,040 Conclusion: High intensity interval training (HIIT) and Continues training increase the VO₂ Max High intensity interval training (HIIT)increase the VO₂ Max than Continues training Of Basketball Players of Muhammadiyah University of Surakarta